STUDENTS' PERCEPTIONS OF SMH BANTEN UIN REGARDING ONLINE ACCOUNT OPEN AT INDONESIAN SHARIA BANK (BSI) - Dede Agustianingsih; Lisah, Cholisah; Nasution, Muhammad Syarif; Hanny Saraswati; Wahyu Hidayat (Institut Agama Islam Negeri Parepare, 2023)
This study aims to analyze the opening of accounts online at Islamic banks. This research uses a quantitative approach with a survey method. Questionnaires were distributed to 19 Muslim students at Sultan Maulana Hasanuddin Banten State Islamic University at the FEBI faculty. The collected data were analyzed using descriptive and inferential statistical methods. The results of the study show that students' perceptions of opening an online account at Bank Syariah Indonesia (BSI) are high.